Design and Development of a Web-Based Community Service Information System at Garut University - Sabilul Muminin, Riyad; Ramdani, Dendi; Fahru Roji, Fikri (RISTEC : Research in Information Systems and Technology, 2023)
The Community Service Program (KKN) is a mandatory activity in universities aimed at enhancing students' competencies in teamwork, leadership, and soft skills partnerships with the community. However, the implementation of KKN often faces challenges such as data inconsistencies, complex registration processes, and difficulties in activity management. This research aims to design and build a website-based KKN information system at Garut University to address these issues. By utilizing website technology, this system is expected to improve the efficiency and effectiveness of KKN implementation.This research employs the Unified Software Development Process (USDP) methodology, which is iterative and adaptive. The stages in USDP, namely inception, elaboration, construction, and transition, are followed systematically. In the inception phase, a needs analysis and feasibility study are conducted to determine the project scope. The elaboration phase produces the system architecture design and functional requirements specifications. The construction phase focuses on implementing the system according to the design that has been made. Finally, the transition phase includes testing, deployment, and system maintenance.The result of this research is a complete and functional website-based KKN information system. The system provides features such as online registration, group management, activity reporting, monitoring, and evaluation. System testing shows that this system is able to meet user needs and provide significant benefits in the implementation of KKN at Garut University. This system can also be an example for other universities that want to improve the quality of KKN implementation through the use of information technology.